2014
DOI: 10.2172/1167129
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion impact of reductant on DWPF and downstream facilities

Abstract: Pitting corrosion, nitrite concentration fell outside that specified in the corrosion control program for HLW 30 A537SRNL-STI-2014-00281 Revision 0 design basis, but in the regions with cracking and cavitation the K-3 corrosion rate is at or greater than the DWPF design basis.5. The cavitation is likely due to the proximity of the refractory coupon to the bubbler orifice but the cracking is related to the Fe° depletion caused by excessive nitric acid used in the glycolic acid CEF campaign.The expected performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(22 citation statements)
references
References 14 publications
1
21
0
Order By: Relevance
“…The glycolate-based solutions were able to maintain more elements in solutions such as Fe, Ni, and Mn. Neither glycolate-or formate-based solutions were able to maintain Hg in boiling solutions, which has been noted in previous testing [2,3].…”
Section: Test Solutionsmentioning
confidence: 63%
See 3 more Smart Citations
“…The glycolate-based solutions were able to maintain more elements in solutions such as Fe, Ni, and Mn. Neither glycolate-or formate-based solutions were able to maintain Hg in boiling solutions, which has been noted in previous testing [2,3].…”
Section: Test Solutionsmentioning
confidence: 63%
“…These more electronegative values are believed to be a function of solution chemistry. Previously, the concentration of soluble mercury was found to influence both Ecorr and the measured corrosion rate [2]. A higher soluble mercury concentration results in more electropositive Ecorr and higher corrosion rates, which can be seen in the data in Table 3-1.…”
Section: Glycolate-based Solutionsmentioning
confidence: 75%
See 2 more Smart Citations
“…Laboratory studies performed at Savannah River National Laboratory (SRNL) indicated that the replacement to glycolic acid allows the reduction and removal of mercury in the Sludge Receipt and Adjustment Tank (SRAT) without significant hydrogen generation [2]. Due to the many advantages that glycolic acid can have over formic acid, testing was performed to evaluate the materials that can be in direct contact and the associated corrosion mechanisms compared with exposure to formic acid [3]. Glycolate, which is the product that may remain after using glycolic acid, can also be carried downstream to High-Level Waste and Low-Level Waste facilities.…”
Section: Introductionmentioning
confidence: 99%